2005
DOI: 10.1007/s00431-005-1759-z
|View full text |Cite
|
Sign up to set email alerts
|

Social interaction and self-esteem of children with cerebral palsy after treatment for severe drooling

Abstract: Interventions to treat drooling should not only be evaluated using measurements of drooling, but the consequences on social interaction and self-esteem should also be assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
72
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 12 publications
1
72
0
1
Order By: Relevance
“…15 A caretaker visual analogue scale score (range 0-10) reflected the severity of drooling, with 0 indicating 'no drooling' and 10 indicating very severe drooling. 5 Based on direct SLT observations and parental reports, the viscosity of saliva was judged before and after BoNT-A (more serous/ more mucus/unchanged).…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 A caretaker visual analogue scale score (range 0-10) reflected the severity of drooling, with 0 indicating 'no drooling' and 10 indicating very severe drooling. 5 Based on direct SLT observations and parental reports, the viscosity of saliva was judged before and after BoNT-A (more serous/ more mucus/unchanged).…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…[2][3][4] Drooling has a serious impact on the children's social interaction, self-esteem, and health. 5 The effectiveness of salivary gland BoNT has been studied extensively, although the debate about which glands should be injected is still going on. Several studies demonstrated that, after BoNT, drooling is significantly reduced.…”
mentioning
confidence: 99%
“…It occurs more frequently and severely in patients with neurological deficits such as cerebral palsy, motor neuron disease or Parkinson's disease 1,2. Persistent drooling may cause adverse events such as problems in social development and dignity of patients, as well as hygiene problems including unpleasant odor, contaminated clothing and furniture, and skin damage by repeated stimulation 3,4. Additionally, in patients with brain injury who have swallowing disorders, posterior drooling may cause coughing, nausea, vomiting, aspiration into the airway, and if severe, aspiration pneumonia 5…”
Section: Introductionmentioning
confidence: 99%
“…They often have a short attention span, a low self-esteem, faced with difficulties in developing relationships with the outside world, family and peers, and are easily frustrated (4). In general, behavioral problems of mentally retarded children can be divided into two categories: external behavior and internal behavior.…”
Section: Effect Of Aerobic Training On the Social Adjustment Of Childmentioning
confidence: 99%